Teaching Design of Face to Face Online with Hypercontent in Education and Training Institutions (LKPD) - Sukri Syamsuri , Andi; Ishaq (International Journal of Psychosocial Rehabilitation, 2020)
The 21st century, which is known as the digital era, has had an impact on changes in all fields, including the world of education, which has come to be called education 4.0. Although it is already in the digital era, implementation in the world of education, especially in learning, has not yet had a significant impact and change; the achievement of 21st-century skills is still a concept. One effort to achieve 21st-century skills is through the implementation of innovative learning by integrating technological, pedagogical, and content knowledge (TPACK), which refers to the blended learning model. Combining face-to-face learning in class (face-to-face) with online learning resources that are packaged through learning tools in the form of hyper content-based modules that are enriched with online learning resources. In this study, a questionnaire collection method was used about the teacher’s perspective on the hyper content LKPD design that can be used in online face-to-face learning. The teacher’s perspective shows that in general, the hyper content LKPD design can be one of the innovative learning solutions for students.